2001
DOI: 10.4315/0362-028x-64.11.1824
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of Beef Chucks with Escherichia coli during Carcass Breaking

Abstract: Samples were obtained by swabbing the whole of the chuck portion on each of the first 500 sides that entered a beef carcass breaking process and the whole of the outer surface of each of the chuck primal cuts that were prepared from those portions. Swabs obtained from groups of 10 sides or cuts that entered or emerged from the process consecutively were combined, and the coliforms and Escherichia coli recovered from each group were enumerated. Coliforms and E. coli were recovered only sporadically from groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 8 publications
1
16
0
2
Order By: Relevance
“…In a study conducted in an Irish beef abattoir, McEvoy et al (2004) reported increases of 2.3 and 2.1 logcfu/cm 2 respectively for total viable bacteria and Enterobacteriaceae counts on the inside round of carcasses during the cutting/boning operations. Similar increases were also reported in E. coli numbers during the boning of beef carcasses (Gill, McGinnis, & Bryant, 2001). Increases in bacterial/pathogen numbers following the cutting and boning operations could be associated to cross-contaminations.…”
Section: Post Slaughter Contamination Of Bovine Meatsupporting
confidence: 62%
See 1 more Smart Citation
“…In a study conducted in an Irish beef abattoir, McEvoy et al (2004) reported increases of 2.3 and 2.1 logcfu/cm 2 respectively for total viable bacteria and Enterobacteriaceae counts on the inside round of carcasses during the cutting/boning operations. Similar increases were also reported in E. coli numbers during the boning of beef carcasses (Gill, McGinnis, & Bryant, 2001). Increases in bacterial/pathogen numbers following the cutting and boning operations could be associated to cross-contaminations.…”
Section: Post Slaughter Contamination Of Bovine Meatsupporting
confidence: 62%
“…Various origins of microbial contamination during cutting/boning were reported in literature. These include carcasses or meat pieces to be processed (McEvoy et al, 2004); meat cutting/boning equipments such as knives, meat conveyors or cutting boards (Gill, Badoni, & McGinnis, 1999;Gill et al, 2001;Jiménez et al, 2009) and soiled surfaces or operators (Sheridan, Lynch, & Harrington, 1992). One of the measures to prevent cross contaminations resulting from contaminated carcasses or meat pieces would be to identify the most contaminated raw materials and to process them separately preferably at the end of the production (Koohmaraie et al, 2012).…”
Section: Post Slaughter Contamination Of Bovine Meatmentioning
confidence: 99%
“…This suggests that at plants with well controlled carcass dressing processes, dressed carcasses heavily contaminated with O157 VTEC must be very rare. Moreover, most of the E. coli found on beef at large North American plants are deposited during the processes for fabricating chilled carcasses to cuts and trimmings (Gill et al ., 2001 ;Youssef et al ., 2013 ).…”
Section: Testing For Pathogens: Hazard Analysis Critical Control Poinmentioning
confidence: 99%
“…Contamination of meat with bacteria from persistent detritus in equipment may be particularly hazardous because, if a pathogenic organism becomes established in the flora, the pathogen may, over lengthy periods, be spread to all product that encounters the contaminated equipment. The risks to consumer health from such contamination in carcass breaking equipment might greatly exceed those from the few pathogens that might survive on effectively decontaminated carcasses from well-controlled dressing processes (Gill et al, 2001).…”
Section: Contamination From Processing Equipmentmentioning
confidence: 99%